Fate of plastic in the environment: From macro to nano by macrofauna. (1st May 2022) - So, Mandy Wing Kwan; Vorsatz, Lyle Dennis; Cannicci, Stefano; Not, Christelle
Abstract: Plastic ingestion has been widely investigated to understand its adverse harms on fauna, but the role of fauna itself in plastic fragmentation has been rarely addressed. Here, we review and discuss the available experimental results on the role of terrestrial and aquatic macrofauna in plastic biofragmentation and degradation. Recent studies have shown how biting, chewing, and stomach contractions of organisms shatter ingested plastic along their digestive tracts. Gut microbial communities can play a role in biodegradation and their composition can shift according to the type of plastic ingested. Shifts in molecular weights, chemical bond forming and breaking, and changes in thermal modification detected in the plastic debris present in the faeces also suggest active biodegradation. A few studies have also shown interactions other than ingestion, such as burrowing, may actively or passively promote physical plastic fragmentation by fauna. We suggest that further investigations into the role of fauna in physical fragmentation and chemical degradation linked to active ingestion and gut associated microbiota metabolism, respectively, should be conducted to better evaluate the impact of these mechanisms on the release of micro- and nano-plastic in the environment. Knowledge on macrofauna other than marine invertebrates and terrestrial soil dwelling invertebrates is particularly lacking, as well as focus on broader types of plastic polymers. Graphical abstract: Image 1 Highlights: Fauna plays a role in plastic fragmentation. Both physical and chemical effects are induced after ingestion of plastic debris. Field studies are limited and should be prioritised in future research.